54.8k views
17 votes
Solve: −(23a−13)+53a=−4

User Tsardines
by
5.7k points

1 Answer

3 votes

Answer:

a = -17/30

Explanation:

So the first step is to distribute the negative sign, if that's a bit confusing think of the negative sign as a -1 instead of just a negative sign, and then think of distributing that negative 1 to the 23a and -13.

Original Equation:

-(23a - 13) + 53a

Distribute negative sign

-23a + 13 + 53a

Group like terms:

(-23a + 53a) + 13

Simplify

30a + 13 = -4

Subtract 13 from both sides

30a = -17

Divide both sides by 30

a = -17/30

User Vansi
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.